Drivers and semantic properties of intellectual capital information in sell-side analysts' reports. Issue 4 (7th November 2016) - Abhayawansa, Subhash; Guthrie, James
Abstract : Purpose: This paper aims to understand the potential usefulness of sell-side analysts' investment recommendation reports as a medium for communicating intellectual capital (IC) information. It explores the manner in which analyst reports supply IC information and the types of companies in relation to which analyst reports supply most IC information. Design/methodology/approach: A content analysis of 64 initiating coverage analyst reports written on Australian companies is performed. The content analysis focuses on three semantic properties of IC disclosures: format (i.e. discursive, numerical-non-monetary, numerical-monetary and visual), news-tenor (i.e. positive, neutral and negative) and time-orientation (i.e. forward-looking, non-time-specific and past-oriented). The paper investigates whether analyst reports contain more IC information on companies providing less IC information through their own channels. For this, the authors test the hypothesised relationship between the extent of IC information and the IC intensity of the analysed company's sector and the systematic risk of the company. Findings: IC information in analyst reports is more discursive than numerical, not significantly more forward-looking in general and balanced between negative or neutral and positive attributions (except for information on company management). However, compared to the semantic properties of corporate reporting media, analyst reports in this study communicate IC information in a manner arguably more useful to investors. A company's systematic risk and sector in which the company operates are associated with the extent of IC information in analyst reports. The findings indicate that analysts' contribution as an IC information provider is greatest for companies providing less IC information directly to the public. Practical implications: The results have implications for policymakers contemplating reforming non-financial reporting regulation and ensuring a level playing field for investors and companies when determining corporate IC disclosure strategy and strategies for investor relations. Originality/value: This is the first study to explore semantic properties and drivers of IC information in analysts' initiating coverage reports. This paper highlights the importance of analyst reports as a medium for communicating IC information that could complement corporate communication media.